MARCIYAN SHASHCEVICH IS A SPEAKER AND PREACHER - Farion, I. Y. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The article offers a new perspective on creative work of educator Markian Shashkevych, including his little explored speeches and sermons in which he appears as reformer and founder of the Ukrainian literary language.